Efektivitas Perlindungan Hukum Kreditur dalam Eksekusi Jaminan Fidusia akibat Wanprestasi: Studi pada Koperasi Simpan Pinjam Tunas Muda - Muhammad Ferdy Fahriza Jusuf; Nirwan Junus; Sri Nanang Meiske Kamba (AHKAM, 2025)
The execution of fiduciary security at the Tunas Muda Savings and Loan Cooperative frequently encounters legal and factual obstacles despite being regulated under Law No. 42 of 1999, and has become increasingly complex following Constitutional Court Decision No. 18/PUU-XVII/2019, which restricts creditors’ unilateral authority to execute collateral. This study aims to analyze the legal effectiveness of creditor rights protection and to identify obstacles in the execution process of fiduciary security at the Tunas Muda Savings and Loan Cooperative. The research employs a socio-legal approach with an empirical legal research design, using primary data obtained through interviews and observations, and secondary data collected through document study, all of which are analyzed using qualitative descriptive techniques. The findings show that the legal effectiveness of fiduciary security execution is not yet optimal; the main obstacles include the non-registration of collateral objects, low legal awareness among debtors, limited litigation costs, and collateral objects that have been transferred or have depreciated in value. These results indicate that Constitutional Court Decision No. 18/PUU-XVII/2019 provides greater protection for debtors but simultaneously reduces efficiency and legal certainty for creditors by requiring court proceedings when default is disputed. The study concludes that enhanced compliance with fiduciary security registration by cooperatives and regulatory improvements are needed to balance protection between creditors and debtors so that fiduciary security execution can proceed more efficiently and fairly.